T-cell/Histiocyte-rich Large B-cell Lmphoma in Pediatric Patients: a Reported Case of a 16-year-old Patient in Clinical Haematology Department of the University Teaching Hospital of Yopougon (Abidjan-Ivory Coast) - Kamara, Ismael; Corcellar Womey, Kodzovi Mawulé; Silué, Dohoma A.; Botti, Réné-Paule; Djeket, Ruth; Kouakou, Boidy; Koffi, Gustave (European Scientific Journal, ESJ, 2023)
T-cell/Histiocyte-rich large B-cell lymphoma (THRLBCL) is a rare pathology, uncommon in children population and the few cases reported, had wide range clinical presentations, including advanced stage, extranodal involvement and bad prognosis. Authors report a case of a 16-year-old male patient with no medical history, who presented a single left axillary adenopathy. T-cell/Histiocyte-rich large B-cell lymphoma was diagnosed by immunohistochemistry and was classified good prognosis. A RCHOP-based chemotherapy was performed with good progress. Authors hope to contribute to the literature on THRLBCL and draw the attention of practitioners to its occurrence in the pediatric population.